When the plot thickens: a rare complication of rheumatoid arthritis. Issue 2 (4th March 2019) - Scheitel, Marianne; Ives, Samuel T.; Nasr, Rawad; Nolan, Marc W.
ABSTRACT: Introduction : Rheumatoid arthritis (RA) is a common illness with many extraarticular manifestations. Rheumatoid pachymeningitis is a rare neurologic complication of this common disease. Here in we present a patient with longstanding RA who developed this uncommon complication. Case description : A 75-year-old woman with longstanding RA presented to the clinic with multiple seizure-like spells per day. Upon admission to the hospital, brain MRI showed enhancement of the meninges. After an extensive workup for possible other infectious or inflammatory causes, the patient was diagnosed with rheumatoid pachymeningitis. Conclusion : Rheumatoid pachymeningitis is a rare complication of RA that usually occurs late in the disease course. It may have many neurologic manifestations include mimicking seizure or stroke and must be considered in patients with RA presenting with neurologic symptoms. Pachymeningitis is treated distinctly from articular RA, so early recognition can lead to appropriate treatment.